PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, KEBIJAKAN HUTANG & KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN - Aulia, Edis Rama; Anita, Widya Febryari (E-Jurnal Akuntansi TSM, 2023)
The purpose of this study focuses on empirically exploring the relationship between the influence of company size, profitability, debt policy, and investment decisions on the value of manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange for the period 2019 to 2022. By using quantitative research types and multiple linear analysis as research methods and sampling using a purposive sampling technique. Whereas the population is manufacturing companies in the consumer goods industry sector in the period 2019 to 2022. Furthermore, the company's annual financial reports are processed using SPSS 2016. The results of the study found that company size, profitability, and investment decisions have a positive effect on firm value. On the other hand, debt policy has a negative and insignificant impact on firm value.